Prevalence of positive group B streptococcal infections among pregnant women in Najran, Saudi Arabia - Alshahrani, Majed S.; Aedh, Abdullah I. (International Journal Of Community Medicine And Public Health, 2023)
Background: Group B streptococcus (GBS) is the most common bacterium to infect women during pregnancy, and vaginal GBS colonisation is a risk factor for newborn GBS illness. The presence of GBS in the woman during labour is thought to be accurately predicted by GBS detection in the final five weeks before to delivery. This study aimed to assess the prevalence of GBS genital infections among pregnant women in Najran, Saudi Arabia. Methods: This cross-sectional retrospective study was conducted at the Armed Forces Hospital in Saudi Arabia. The study included data from electronic health records of all pregnant women who were examined and tested for genitourinary GBS infection in the hospital. Data was retrieved using a pre-designed form that included characteristic of the pregnant women, the gestational age at the time of GBS testing, and swap result of GBS. For each positive GBS swap, the antibiotic sensitivity against twenty-one antibiotics was recorded. Results: A total of 2308 pregnant women were included. The mean age was 32±7 years. The prevalence of positive GBS swap was 10.4%. The average gestational age of the women who had a positive swap was 34±9 weeks. Regarding antibiotics sensitivity, Penicillin (86.7%), Ampicillin (61.8%) and cephalexin (55.6%) were among the antibiotics that showed the highest sensitivity rates. Conclusions: We found an isolation rate of 10.4% of GBS among pregnant women who attended Najran Armed Forces Hospital. We recommend more comprehensive screening programs and strict management plans to avoid antimicrobial resistance to spread among these GBS strains.